2023
DOI: 10.1007/s00702-023-02648-z
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of late-life depression and its pathobiology: a brain network dysfunction disorder

Abstract: Depression is frequent in older individuals and is often associated with cognitive impairment and increasing risk of subsequent dementia. Late-life depression (LLD) has a negative impact on quality of life, yet the underlying pathobiology is still poorly understood. It is characterized by considerable heterogeneity in clinical manifestation, genetics, brain morphology, and function. Although its diagnosis is based on standard criteria, due to overlap with other age-related pathologies, the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 244 publications
0
6
0
Order By: Relevance
“…Despite the heterogeneity, there are some distinctive neurocognitive and behavioural changes that appear to be attributable to geriatric depression and that are characteristic of a large group of patients who do not have neurological disease. 27 …”
Section: Presentation/characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the heterogeneity, there are some distinctive neurocognitive and behavioural changes that appear to be attributable to geriatric depression and that are characteristic of a large group of patients who do not have neurological disease. 27 …”
Section: Presentation/characteristicsmentioning
confidence: 99%
“…The incidence of depression may be 30% in vascular dementia and in AD, and over 40% in Parkinson’s disease dementia and Huntington’s disease dementia. 27 A study published in 2023 shows that depression is a comorbidity often associated with dementia and also that depression increases the risk of dementia. 13 People with any type of dementia have a high incidence of major depression, particularly if they have vascular dementia or Parkinson’s disease dementia—these patients often have more insight and awareness of their condition than people with AD.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for inconsistent results is heterogeneity in LLD [ 22 , 23 , 71 ]. Here, we define heterogeneity as variability due to ‘true’ etiological differences between patients, as opposed to construct or analytical variability leading to experimentally introduced differences between LLD samples.…”
Section: Challenges and Future Directions In The Identification Of Ll...mentioning
confidence: 99%
“…The former refers to depressive disorders with the first onset before age 60 and recurrence after age 60, whereas the latter refers to depressive disorders with the first episode after age 60 ( Ly et al, 2021 ). With global population aging, the prevalence of LLD is increasing every year ( Jellinger, 2023 ). A recent report showed that the prevalence of depressive symptoms in older adults is 20% and is highly heterogeneous ( Tang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%